2018
DOI: 10.1016/j.jogoh.2017.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of vaginally administered lyophilized Lactobacillus crispatus IP 174178 in the prevention of bacterial vaginosis recurrence

Abstract: In women with recurrent BV after antibiotics, treatment with Lc IP 174178 administered over four menstrual cycles, could significantly reduce the rate of recurrence and increase the time to recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 26 publications
1
43
0
5
Order By: Relevance
“…The search identified 2949 unique articles but only 34 studies were eligible (flow diagram in Figure ) . Thirteen studies reported 14 results on BV and/or molecular VMB composition (Table ), 12 studies reported 12 results on VVC (Table ), and 14 studies reported 15 results on vaginal probiotic strain detection using molecular techniques (Table S1). The selected studies evaluated 22 different vaginal probiotics (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search identified 2949 unique articles but only 34 studies were eligible (flow diagram in Figure ) . Thirteen studies reported 14 results on BV and/or molecular VMB composition (Table ), 12 studies reported 12 results on VVC (Table ), and 14 studies reported 15 results on vaginal probiotic strain detection using molecular techniques (Table S1). The selected studies evaluated 22 different vaginal probiotics (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (11/13) were randomised controlled trials, including six with placebo controls, two with ‘no intervention’ controls, four with metronidazole or clindamycin controls, and one with a vaginal pH‐lowering tablet control (two trials included both placebo/‘no intervention’ and antibiotic controls) (Table ). Five clinical trials were judged medium risk and the other six high risk . The two remaining studies (both judged high risk) were pre‐post intervention studies in women receiving a vaginal probiotic without an antibiotic …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In addition to its presence as an indigenous bacterium in the vagina, some probiotic uses of L. crispatus have also been studied. 56 L. crispatus showed a protective effect in treatment of recurrent BV 57 and urinary tract infection (UTI). 58,59 The latter was supported by the observation that UTI recurrence was associated with abnormal vaginal flora.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a 28% longer time to reoccurrence in the probiotic group ( P = .0298). This study looked at adverse effects and found the overall tolerability to be 92.2% and did not find differences between the groups . This specific formulation is commercially available.…”
Section: Use Of Cam For Bvmentioning
confidence: 99%